A rare cause of acute urinary retention in a young man: a median raphe penile cyst - Kamarulzaman, Mohd Nazli; Chik, Azhani; Ghazali, Hamid (Academy of Family Physicians of Malaysia, 2021)
Background: A penile median raphe cyst is an uncommon congenital lesion that is formed due to failure of the median raphe to close completely during embryo development. The majority of the cysts are asymptomatic and often go unnoticed. Here, we report acute urinary retention as a very rare complication of a penile median raphe cyst. Case presentation: A 21-year-old single man presented with a sudden onset of acute urinary retention of one days’ duration. Urethral catheterization was done at the Emergency Department and this drained 800 ml of urine. On further questioning, he claimed that he had had a painless nodule at the glans penis since childhood. The swelling increased in size in the past week causing discomfort. He denied any history of genitalia trauma or recent sexual intercourse. On examination, there was a bluish lesion over the ventral aspect of the glans penis measuring about 3 x 2 cm. The lesion was later excised and histopathology revealed a median raphe cyst of the penis. Conclusion: A penile median raphe cyst is a rare lesion. Acute urinary retention caused by this lesion is very rare